Implementation of A Motorcycle Vehicle Security System with Arduino-Based Fingerprint, Global Positioning System and Short Message Service Gateway - Randi Rizal; Aso Sudiarjo; Nur Widiyasono; Dede Rizal Nusamsi; Muhammad Faiz (IJAIT (International Journal of Applied Information Technology), 2024)
The increase in demand for motorized vehicles, especially motorcycles, from 2016 - 2021 has recorded an increase of 5.03% per year. Along with the increasing number of people using motorbikes as their main means of transportation, there is a growth in motorcycle theft. One cause of the increase in these cases is that the motorcycle security system still relies on the lock system. So, it is necessary to improve security with unique modern keys that can only be accessed by specific people, one of which is a security system using biometric technology. This research has combined motorcycle security systems using fingerprint, GSM and GPS modules based on Arduino Uno. The results of testing the fingerprint module scanning time obtained an average scanning time of 1.04 seconds. Testing the SIM800L GSM module obtained an average processing time of receiving SMS and sending back a response to a registered number, which is 9.32 seconds and the results of testing the accuracy of data retrieval between the U-blox Neo-6m GPS module and GPS on the Oppo A3S brand smartphone, with the calculation of the average difference distance of 0.75 Meters. Motorcycle vehicle security was successfully implemented by utilizing the fingerprint module, GPS module and GSM module as an intermediary in the form of SMS between the user and the microcontroller so that it functions as layered security.